ANALISIS PENGENDALIAN MANAJEMEN MUTU PROJECT PENINGKATAN JALAN PROPINSI DI SUMATERA UTARA - Erwin harun (JURNAL MANAJEMEN DAN BISNIS, 2019)
The problems that arise in the control of qualitymanagement depart from: a) Weakness quality of human resource in the quality control system will be able to affect the measurement of the quality assurance aspect of the provincial road improvement.b)Quality control is not optimal in the implementation of the quality control of the province.c) Human resource commitmen to the rules relating to the quality, procedure of guidelines applicable low. Studi show that the quality management control road improvement project in North Sumatra province was determined by tri-partied among regulators, owners, contractors and consultants implementing the project and the quality assurance standards of quality and runs with good control.